Exact Solutions for the Flow of Fractional Maxwell Fluid in Pipe-Like Domains (Advances in Applied Mathematics and Mechanics, 2018)
This paper presents an analysis of unsteady flow of incompressible fractionalMaxwell fluid filled in the annular region between two infinite coaxial circularcylinders. The fluid motion is created by the inner cylinder that applies a longitudinaltime-dependent shear stress and the outer cylinder that is moving at a constant velocity.The velocity field and shear stress are determined using the Laplace and finiteHankel transforms. Obtained solutions are presented in terms of the generalized G andR functions. We also obtain the solutions for ordinary Maxwell fluid and Newtonianfluid as special cases of generalized solutions. The influence of different parameterson the velocity field and shear stress is also presented using graphical illustration.Finally, a comparison is drawn between motions of fractional Maxwell fluid, ordinaryMaxwell fluid and Newtonian fluid.